Simulation And Optimization Of Dehydration Reactor In Acrylic Acid Production Using Glycerol - Xavier, Belinda Anne (Universiti Sains Malaysia, 2017)
The production of acrylic acid using glycerol feedstock is gaining importance worldwide and thus the process needs to be studied and optimized fully so that the yield and quality of acrylic acid are assured before its implementation in industrial scale. With the development of simulating software such as Aspen Plus, it is possible to simulate and optimize a process with desired end-product characteristics. However, there is no fixed idea on the optimum reaction conditions to produce maximum yield of acrylic acid. In this work, Aspen Plus was used to simulate and optimize an isothermal fixed bed plug flow dehydration reactor where glycerol was dehydrated into acrolein and side-products such as acetaldehyde, ethylene, carbon monoxide, hydrogen and coke in the presence of ZSM-5 zeolite catalyst. The simulation results obtained were first compared with that from literature. The simulated results obtained by Aspen Plus showed that it is acceptable since the simulation values obeyed that of the literature with an average conversion and yield errors of 4.84% and 26.25% respectively. Sensitivity analysis on the same RPLUG reactor model showed that reactor temperature, pressure and glycerol concentration had significant effects on glycerol conversion and acrolein yield. The glycerol conversion was found to increase with reactor temperature and pressure but decreased with WHSV and glycerol concentration. Meanwhile, acrolein yield increased with the rise in reactor temperature till 420°C, WHSV and glycerol concentration up to 60 wt%. Lastly, optimization study on the reactor model resulted in maximum acrolein yield of 42.85% which is achieved at optimum variables of 450.78°C, 1 bar and 60 wt% glycerol concentration.